Transforming the rural economy through recycling agricultural waste - K. C., Shinogi; Vishwakarma, A. K.; Datta, S. P.; Sahu, Asha; Bharati, K.; Lakaria, B. L.; Shirale, A. O.; Kamble, A. L.; Singh, R. K.; Wanjari, R. H.; Lal, Narayan; Srivastava, S.; et al. (Indian Farming, 2025)
Under the circumstances of increasing cultivation costs particularly due to the hike in fertilizer costs coupled with second-generation problems related to deteriorating soil health and declining factor productivity, farmers are encouraged to adopt agricultural waste recycling technologies to reduce reliance on external nutrient inputs. During 2017-2024, ICAR-Indian Institute of Soil Science (IISS), Bhopal demonstrated different on-farm waste management techniques to the farmers of Khamkheda, Kalyanpura, Kanchbavli, and Berupura villages of Bhopal, Madhya Pradesh in connection with the ICAR initiative ‘Farmer FIRST Programme’. With composting,though a considerable amount of production cost was saved, a few farmers of these villages made use of the ‘vermicomposting’ technology to set up small-scale enterprises in the area. This article highlights the journey of a young Agripreneur who successfully transformed his farming and farmbased livelihood in a short time period, with the support of agricultural information sources andtechnology providers near his village Kalyanpura located in the Bhopal district of Madhya Pradesh.